Annual report 2019: CGIAR Research Program on Climate Change, Agriculture and Food Security - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Annual technical report for the CGIAR Consortium describing progress to date, significant achievements and successes in 2019, flagship products and tools, and publications.